Investigation of Axial Flux In-Wheel Motor Performances Based on Multiphysics Analysis - DOU Haishi; ZHANG Youtong; LI Tao; AI Qiang (E3S Web of Conferences, 2021)
The axial flux with amorphous alloy stators has the virtues of high power density, high torque density, compact structure. But specific to the disadvantage of restricted space of in-wheel, the compact axial flux in-wheel motor was proposed in this paper. The in-wheel motor’s performance affects the dynamic and security of electric vehicles directly. And the electromagnetic loss has a significant impact on in-wheel motor performance. To demonstrate the influence of electromagnetic loss on the thermal behavior of the machine, thermal analyses employing magneto-thermal coupling simulations have been performed. Then the experimental prototype was manufactured and tested. The simulation of the output power model was verified by test value, proving that the magneto-thermal coupling simulation is feasible. Therefore, this design technique provides a reference for the in-wheel motor structure.